Gender Pay Gap dalam Perspektif Ekonomi Syariah: Analisis Normatif Prinsip Keadilan dan Kesetaraan Upah - Nur Tarobby Awwalul Ramadhan; Sifwatir Rif'ah (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2025)
The gender pay gap is a labor market phenomenon that reflects gender-based structural inequality and remains a serious challenge in efforts to achieve social justice. Wage differences between men and women are often not fully explained by productivity, education, or work experience, indicating the presence of systemic discrimination. This study aims to analyze the gender pay gap from the perspective of Islamic economics by emphasizing the principles of justice (al-‘adl), equality (al-musawah), and welfare. The research employs a library research method with a qualitative normative approach through thematic analysis of Islamic economic literature, academic journals, statistical data, as well as Qur’anic sources and scholarly perspectives. The findings reveal that the gender pay gap is influenced by structural discrimination, social norms, and the weak implementation of equitable wage systems. This study contributes to strengthening the normative framework of Islamic economics as an ethical and conceptual foundation for formulating fair and gender-equitable wage policies.